Thermo-fluid dynamics of non-newtonian casson fluid in expanding-contracting channels with joule heating and variable thermal properties - Shahid Rafiq; Babar Ahmad Bilal; Aysha Afzal; Jagadish V. Tawade; Nitiraj V. Kulkarni; Barno Abdullaeva; Taoufik Saidani; Manish Gupta (Partial Differential Equations in Applied Mathematics)
This study focuses on the thermo-fluid dynamics of non-Newtonian Casson fluid within a porous channel with expanding and contracting walls, a configuration of significant relevance in industrial applications like cooling systems and biomedical processes such as biofluid transport. The investigation accounts for critical factors such as Joule heating, thermal radiation, porosity, and the temperature dependence of viscosity and thermal conductivity. The governing equations are reduced to ordinary differential equations using similarity transformations and solved with the Least Square Method (LSM). The findings reveal that the Hartmann number and Eckert number strongly influence velocity and temperature profiles. Thermal radiation elevates the core fluid temperature while heat sinks reduce it near the channel walls. Viscosity models demonstrate notable effects on flow resistance and heat transfer. The findings will provide significant applications requiring efficient thermal management and precise control of fluid dynamics, making the results valuable for engineering and biomedical advancements.